The boy who lost his face - Sachar, Louis, 1954- (New York, NY : Scholastic Inc., 1989)
David receives a curse from an elderly woman he has helped his schoolmates attack, and he learns to regret his weakness in pandering to others for the sake of popularity before new friends and a very nice girl help him to be a stronger, more assertive person.
G3
Keywords: Schools -- Fiction; Bullies -- Fiction; Interpersonal relations -- Fiction